The Role of Ground Handling Management in Improving Aircraft Turnaround Time Efficiency - Pribadi, Mochamad Reza (Dinasti International Journal of Economics, Finance & Accounting, 2026)
Ground handling plays a crucial role in ensuring efficient aircraft operations, particularly in minimizing turnaround time (TAT). This study aims to analyze the role of ground handling management in improving operational efficiency in air transportation. The method used in this research is a qualitative approach through literature review and analysis of secondary data from aviation reports and previous studies. The results indicate that effective coordination, workforce competency, and the use of technology significantly influence turnaround efficiency. Delays in ground handling activities such as baggage handling, refueling, and passenger boarding can directly impact flight schedules. Therefore, integrated management and operational optimization are essential to enhance service quality and airline performance.